A Tracer Streamline Practice for Re-Evaluation Waterflood Pattern to Introduce a Cyclic Water Injection Scheme - Dike Fitriansyah Putra; Lazuardhy Vozika Futur; Mursyidah Umar (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Waterflood introduces in the oil field a couple of years ago. Several waterflood schemes have been implemented in the fields to get the best incremental oil, such as peripheral injection, pattern waterflood, and etcetera. Many waterflood schemes are not working properly to boost the oil recovery due to unpredicted and unexpected water tide array. Then, the tracer practice started to be used for getting a better picture of the transmissibility reservoir as well as the direction of water pathway. This practice honors the parameters, such pressure, water cut, GOR, and rates. The streamline modeling is used to map the tracer, and it concludes that the selection of location of the injector should be based on the highest oil recovery achieved. Subsequently, the cyclic water injection method is one alternative. Apparently, this approach yields a quantify incremental recovery. This research utilizes the pressure different approach to figure out the route of water in the formation. The inter-well tracer technique in this modeling study is a tool to review communication between injectors and producers in the existing pattern. Many scenario should be tried to find the best options for the new pattern opportunities. In parallel, a innovative scheme of waterflood technique should be implemented too for escalating oil recovery. The stream pathway observes a new potential of the waterflood scheme. It is called "cyclic injection" scheme. The novelty of this approach is the ability to solve the poor sweep efficiency due to improper pathway of water influx in the oil bearing".